2010
DOI: 10.1002/cmdc.201000184
|View full text |Cite
|
Sign up to set email alerts
|

Novel 3‐Carboxy‐ and 3‐Phosphonopyrazoline Amino Acids as Potent and Selective NMDA Receptor Antagonists: Design, Synthesis, and Pharmacological Characterization

Abstract: The design and synthesis of new N1-substituted 3-carboxy- and 3-phosphonopyrazoline and pyrazole amino acids that target the glutamate binding site of NMDA receptors are described. An analysis of the stereochemical requirements for high-affinity interaction with these receptors was performed. We identified two highly potent and selective competitive NMDA receptor antagonists, (5S,alphaR)-1 and (5S,alphaR)-4, which exhibit good in vitro neuroprotective activity and in vivo anticonvulsant activity by i.p. admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…In this study, we explore the structural and pharmacological properties of a series of ligands based on (S)-5-[(R)-2-amino-2-carboxyethyl]-4,5-dihydro-1H-pyrazole-3-carboxylic acid (ACEPC) (22). Competitive NMDA receptor antagonists in this series have been evaluated as potential neuroprotective and radioligand imaging agents (22,23).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we explore the structural and pharmacological properties of a series of ligands based on (S)-5-[(R)-2-amino-2-carboxyethyl]-4,5-dihydro-1H-pyrazole-3-carboxylic acid (ACEPC) (22). Competitive NMDA receptor antagonists in this series have been evaluated as potential neuroprotective and radioligand imaging agents (22,23).…”
Section: Significancementioning
confidence: 99%
“…Competitive NMDA receptor antagonists in this series have been evaluated as potential neuroprotective and radioligand imaging agents (22,23). Furthermore, preliminary functional results suggested that addition of halogen substituents to one of these ligands, FRA-19 {(S)-5-[(R)-2-amino-2-carboxyethyl]-1-phenyl-4,5-dihydro-1H-pyrazole-3-carboxylic acid}, resulted in modest preference for GluN1/2A over GluN1/2B receptors, as seen for compounds ST1 {(S)-5-[(R)-2-amino-2-carboxyethyl]-1-(4-fluorophenyl)-4,5-dihydro-1H-pyrazole-3-carboxylic acid} and ST6 {(S)-5-[(R)-2-amino-2-carboxyethyl)-1-(4-bromophenyl)-4,5-dihydro-1H-pyrazole-3-carboxylic acid} (23).…”
Section: Significancementioning
confidence: 99%
“…In this study, we examined the neuroprotective effects of Bv8 in murine cortical cell cultures and in organotypic hippocampal slices exposed to OGD, two in vitro models of cerebral ischemia routinely in use in our laboratory that allow chronic treatment with drugs in a relatively isolated environment that closely reproduces what occurs in vivo (Conti et al, 2010;Gerace et al, 2012a). We also examined the role of prokineticins in the induction of OGD tolerance and the expression of prokineticins and prokineticin receptors following NMDA preconditioning in organotypic hippocampal slices.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, preliminary evaluation of GluN2 subunit selectivity suggested that the racemic mixture (±)-3 displayed a preference for inhibition of NMDA receptors containing GluN2A or GluN2B subunits compared to receptors with GluN2C or GluN2D subunits. 10 …”
Section: Introductionmentioning
confidence: 99%